Influence of efficacy beliefs on the learning experiences of children with cancer in the hospital setting. - Crossland, Andrea. (University of Ottawa (Canada), 2001)
When a chronic medical condition, such as cancer, imposes limitations on a child's physical and/or cognitive abilities, the opportunities for the child to feel academically successful are reduced and thus these children are at risk of becoming underachievers and failures in their own eyes. These children miss out on experiences that normally lead to a development of self and a sense of control over their environment. From a social cognitive perspective, learning and educational development are dependent on whether students perceive that they can control the factors which allow them to manage their learning conditions and situations. However, since the constraints of being hospitalized and health impaired affect such perceptions, there should be an improved understanding of how self-efficacy beliefs contribute to oncology students' learning in the hospital setting. Therefore, the objectives of this research were to examine, through a multiple case study approach, how self-efficacy beliefs influence oncology students' motivation to learn in the hospital setting, their ability to regulate and master academic activities, their affective response to their hospital learning experiences, and their personal adjustment under adverse conditions. Attention was also devoted to these students' acquisition and use of self-regulatory skills. The cases presented in this study focus on the learning experiences of 5 hospitalized oncology students receiving educational services in one large Ontario children's hospital. The children ranged in age from 9 to 13 years. Data were collected using multiple qualitative methods over a 3 month period and were analyzed from a constructivist perspective. Results indicated that, motivationally, hospital education was valued most when the children's goal of returning to the community school was proximal and thus the purpose of the instruction was evident. For those students with no immediate expectation of returning to the classroom, the hospital education program provided them with important social contacts. Academic efficacy beliefs were strongly linked to the way oncology students attributed their difficulties---either to a lack of effort or ability. In the absence of peer social comparative information, the oncology students depended heavily on their hospital teachers to be credible sources of learning and development information. These children also depended on their teachers and mothers to structure their learning experiences and could not be considered self-regulated learners. Ultimately, the greatest source of academic anxiety for the oncology students stemmed from their inability to control the effects of their illness on their physical and academic capabilities and the difficulties inherent in the instructional context. Although this study focused on the theoretical and psychological aspects of learning and the child with cancer, the ability of a child to succeed is still partially dependent on the policies, practices, and scope of the educational program. Therefore, this thesis concludes by linking the theoretical findings with practical recommendations for the improvement of educational services offered to hospitalized oncology students.
Keywords: Education, Educational Psychology.